Growth of two dimensional silica and aluminosilicate bilayers on Pd(111): from incommensurate to commensurate crystalline. Issue 21 (18th May 2017) - Jhang, Jin-Hao; Zhou, Chao; Dagdeviren, Omur E.; Hutchings, Gregory S.; Schwarz, Udo D.; Altman, Eric I.
Abstract : 2D silicate lattice strain energy was significantly reduced by Al-doping resulting in a structural transition from incommensurate to commensurate crystalline. Abstract : Two-dimensional (2D) silica (SiO2 ) and aluminosilicate (AlSi3 O8 ) bilayers grown on Pd(111) were fabricated and systematically studied using ultrahigh vacuum surface analysis in combination with theoretical methods, including Auger electron spectroscopy, X-ray photoelectron spectroscopy, low-energy electron diffraction (LEED), scanning tunneling microscopy (STM), and density functional theory. Based on LEED results, both SiO2 and AlSi3 O8 bilayers start ordering above 850 K in 2 × 10 −6 Torr oxygen. Both bilayers show hexagonal LEED patterns with a periodicity approximately twice that of the Pd(111) surface. Importantly, the SiO2 bilayer forms an incommensurate crystalline structure whereas the AlSi3 O8 bilayer crystallizes in a commensurate structure. The incommensurate crystalline SiO2 structure on Pd(111) resulted in a moiré pattern observed with LEED and STM. Theoretical results show that straining the pure SiO2 bilayer to match Pd(111) would cost 0.492 eV per unit cell; this strain energy is reduced to just 0.126 eV per unit cell by replacing 25% of the Si with Al which softens the material and expands the unstrained lattice. Furthermore, the missing electron created by substituting Al 3+ for Si 4+ is supplied by Pd creating a chemical bond to the AlSi3 O8 bilayer, whereas van der Waals interactions predominate for the SiO2 bilayer. The results reveal how the interplay between strain, doping, and charge transfer determine the structure of metal-supported 2D silicate bilayers and how these variables may potentially be exploited to manipulate 2D materials structures.